1971
DOI: 10.1111/j.1476-5381.1971.tb07171.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of 4‐hydroxypropranolol, a metabolite of propranolol

Abstract: Summary1. 4-Hydroxypropranolol, a metabolite produced after oral administration of propranolol, has been shown to be a /3-adrenoceptor blocking drug. It is of similar potency to propranolol in antagonizing the effects of isoprenaline on heart rate and blood pressure in cats and against isoprenaline protection of guinea-pigs from bronchospasm. It is not cardioselective. 2. In rats depleted of catecholamine 4-hydroxypropranolol produced an increase in heart rate, suggesting that it has intrinsic sympathomimetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 12 publications
4
76
1
Order By: Relevance
“…This assumes, however, that only unchanged drug contributes to the pharmacological effect. It has been shown in dogs that 4'-hydroxypropranolol and propranolol are equipotent in their /3-adrenoceptor blocking properties (Fitzgerald & O'Donnell, 1971). 4'-Hydroxypropranolol is formed in significant amounts only after oral dosing in man (Paterson et al, 1970) and indirect evidence based on a disparity between the extent of f3-adrenoceptor blockade achieved after oral and intravenous propranolol suggested that 4'-hydroxypropranolol contributes significantly to /3-adrenoceptor blockade after a single oral dose of drug (Cleavland & Shand, 1972;Coltart & Shand, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…This assumes, however, that only unchanged drug contributes to the pharmacological effect. It has been shown in dogs that 4'-hydroxypropranolol and propranolol are equipotent in their /3-adrenoceptor blocking properties (Fitzgerald & O'Donnell, 1971). 4'-Hydroxypropranolol is formed in significant amounts only after oral dosing in man (Paterson et al, 1970) and indirect evidence based on a disparity between the extent of f3-adrenoceptor blockade achieved after oral and intravenous propranolol suggested that 4'-hydroxypropranolol contributes significantly to /3-adrenoceptor blockade after a single oral dose of drug (Cleavland & Shand, 1972;Coltart & Shand, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…They showed that an active metabolite of propranolol, 4-hydroxy propranolol, can be detected in the plasma only after oral administration. This metabolite is not measured by the standard propranolol assay, but since it is equipotent to propranolol (Fitzgerald & O'Donnell, 1971) and achieves approximately the same circulating concentrations as the parent drug shortly after an oral dose (Paterson et al, 1970), the effects of the metabolite will add to those of propranolol. The presence of this metabolite after oral but not intravenous propranolol would appear to account for the twofold difference in the effective propranolol concentration by the two routes of administration.…”
Section: Cardioselectivitymentioning
confidence: 99%
“…Concentration-response curves of propranolol were parallel but the oral concentration-response curve was shifted to the left of the i.v. curve, indicative of probable pharmacodynamic interference by a metabolite, an observation first made by Coltart & Shand (1970) and thought to reflect the presence of 4-hydroxypropranolol, a metabolite which appears to exert similar 0-adrenoceptor blocking activity to that of propranolol (Fitzgerald & O'Donnell, 1971). The lack of any such shift in pindolol concentration-response curves, even in those individuals with the lowest systemic bioavailability, indicates that its metabolites do not appear to exert any effects on ,-adrenoceptors.…”
Section: Resultsmentioning
confidence: 93%